PROGRAM FOR IMPLEMENTING FAMILY HOPE IN SINGKUP VILLAGE PURBARATU SUB-DISTRICT TASIKMALAYA CITY - Chandra Ardiana; Asep Nurwanda; Candra Firmanto (JGSRD: Journal of Government Science and Rural Development, 2023)
This research was motivated by observations and found a problem, namely the limited socialization of the implementing parties regarding the objectives of the Family Hope Program, the inappropriate target of the recipients of the Family Hope Program in Singkup Village because they are families with the category of being able to, and the limitations of the companion team in conducting data collection. The problem in this research is "How is the Implementation of the Family Hope Program in Singkup Village, Purbaratu District, Tasikmalaya City?" The type of research used is qualitative, using a descriptive approach. Primary data 9 informants. Data collection techniques are interviews, observation, and documentation. The technical analysis is data collection, data reduction, data presentation, and conclusion drawing/verification. Based on the discussion: 1) Implementation of the Family Hope Program in Singkup Village, Purbaratu District, Tasikmalaya City is not optimal. 2) The obstacle is that there are still beneficiaries who are registered incorrectly because they are capable families and the distribution time is not in accordance with the provisions. 3) Efforts are being made, namely coordination between policymakers and field implementers.